Culturally-sensitive complaints of depressions and anxieties in women - Halbreich, Uriel; Alarcon, Renato D.; Calil, Helena; Douki, Saida; Gaszner, Peter; Jadresic, Enrique; Jasovic-Gasic, Miroslava; Kadri, Nadia; Kerr-Correa, Florence; Patel, Vikrarn; Sarache, Xarifa; Trivedi, J. K. (Elsevier B.V., 2007)
Background: Current classifications of Mental Disorders are centered on Westernized concepts and constructs. Cross-cultural sensitivity emphasizes culturally-appropriate translations of symptoms and questions, assuming that concepts and constructs are applicable.Methods: Groups and individual psychiatrists from various cultures from Asia, Latin America, North Africa and Eastern Europe prepared descriptions of main symptoms and complaints of treatment-seeking women in their cultures, which are interpreted by clinicians as a manifestation of a clinically-relevant dysphoric disorder. They also transliterated the expressions of DSM IV criteria of main dysphoric disorders in their cultures.Results: In many non-western cultures the symptoms and constructs that are interpreted and treated as dysphoric disorders are mostly somatic and are different from the Western-centered DSM or ICD systems. In many cases the DSM and ICD criteria of depression and anxieties are not even acknowledged by patients.Limitations: the descriptive approach reported here is a preliminary step which involved local but Westernized clinicians-investigators following a biomedical thinking. It should be followed by a more systematic-comprehensive surveys in each culture.Conclusions: Westernized concepts and constructs of mental order and disorders are not necessarily universally applicable. Culturallysensitive phenomena, treatments and treatment responses may be diversified. Attempts at their cross-cultural harmonization should take into consideration complex interactional multi-dimensional processes. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: depression; anxiety; women; cross-cultural